1956
DOI: 10.1161/01.cir.14.5.815
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Correlative Study of the Electrocardiogram in Electrolyte Imbalance

Abstract: There is no general agreement concerning the action of specific electrolyte disorders and acid-base balance upon concentrations by determining their intracellular/extracellular relationships. Crismon and associates8 could not relate the intracellular potassium concentration to typical electrocardiographic events in hyperkalemia. Bellet, too, could not establish a definite relationship of the electrocardiographic changes to skeletal muscle potassium content.9 He considered, among other possibilities, that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0
3

Year Published

1964
1964
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 31 publications
3
12
0
3
Order By: Relevance
“…The Heart rate P width P-R segment (end P to beginning QRS) T-syst (interval from R peak to end T) Diaz (interval from beginning P to end T) S-T interval specificity was 85% for potassium > 5 mmol/L. These results are similar to those reported in the mid-1950s by Dreifus and Pick, 3 who found a 54% sensitivity for one clinician in recognition of hyperkalemia from the ECG. Clearly, even the highest reported sensitivity among those studies (58.5%) is unacceptable for detecting a potentially lethal condition.…”
supporting
confidence: 86%
“…The Heart rate P width P-R segment (end P to beginning QRS) T-syst (interval from R peak to end T) Diaz (interval from beginning P to end T) S-T interval specificity was 85% for potassium > 5 mmol/L. These results are similar to those reported in the mid-1950s by Dreifus and Pick, 3 who found a 54% sensitivity for one clinician in recognition of hyperkalemia from the ECG. Clearly, even the highest reported sensitivity among those studies (58.5%) is unacceptable for detecting a potentially lethal condition.…”
supporting
confidence: 86%
“…11 It is now known that at the tissue level, hyperkalemia reduces myocardial conduction velocity and accelerates the repolarization phase, producing well-described changes on the surface electrocardiogram (ECG), including a narrow, symmetrical T wave, prolonged PR interval, diminished P-wave amplitude, QRS widening, and ultimately a sinusoidal ''QRST'' that terminates in asystole or ventricular fibrillation. [12][13][14][15][16][17] Other ECG changes that have been associated with hyperkalemia include conduction blocks (fascicular block, bundle branch block, seconddegree heart block, and complete heart block) and block of bypass tracts with loss of the delta wave in patients with Wolff-Parkinson-White syndrome. [18][19][20] Although few maneuvers are necessary for the initial management of hyperkalemia, prior studies in hospitalized patients have shown an average delay of 2.1 hours after laboratory notification before initiation of treatment for severe hyperkalemia.…”
mentioning
confidence: 99%
“…For examples, peaked T waves and widen T waves could be observed in some chest leads during mild hyperkalemia, and flatten P waves in some limb and chest leads. Other vulnerable variable such as increased PR interval, QRS interval, and RR interval could be seen during mild to severe hyperkalemia [2,3]. However, the choice of exact features in response to hyperkalemia is difficult because of the variability of features.…”
Section: Introductionmentioning
confidence: 99%